O Discurso da industrialização do ensino na política nacional de educação a distância. - Costa, Antonio Roberto Faustino da (2008)
Analysis how the industrialization of teaching is in formation discourse is the dominant discourse around the national policy for distance education. Adopts as a reference the "Theory of industrialization of teaching", who designs the EAD as a form characterized by the model of industrial production. In light of the theoretical and methodological framework of Analysis of Discourse by french orientation, examines the policy of EAD as a discursive practice governed by FD dominant. Constitute corpus as discursive ten texts, involving documents and publications, produced by bodies linked to the Federal Government in the period that includes the decades of 1950 and 2000. Evidence that the discourse of the industrialization of teaching prevails between the discursive practices that are struggling around the policy of EAD. Indicates that the practice discursive influence discursive practices not reflected in this policy. Concludes that the discourse of the industrialization of teaching governing the discursive practice that guided the national policy for distance education.